PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KETERAMPILAN LITERASI INFORMASI MAHASISWA PGMI UIN SULTAN THAHA SAIFUDDIN JAMBI - Nina Ninazazqia (Jurnal Lazuardi, 2026)
This study aims to analyze the influence of social media use on the information literacy skills of students in the Elementary School Teacher Education (PGMI) Program at UIN Sultan Thaha Saifuddin Jambi. The research employed a qualitative approach with a field research design to obtain an in-depth understanding of students’ practices in using social media and their information literacy skills based on empirical conditions in the field. The research subjects were selected through purposive sampling, involving PGMI students with a relatively high intensity of social media use in academic activities, supported by additional informants consisting of course lecturers. Data were collected through in-depth interviews, direct observation, and documentation. Data analysis was conducted qualitatively through the stages of data reduction,data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that social media use has an influence on the information literacy skills of PGMI students. Social media facilitates access to academic information and increases students’ interest and engagement in the learning process. However, this convenience is not fully accompanied by students’ ability to evaluate the credibility and validity of information sources, resulting in a tendency to use information without adequate verification. The discussion highlights that information literacy functions as a controlling mechanism in the use of social media. Strengthening information literacy skills is necessary to ensure that social media is utilized critically, responsibly, and in accordance with academic standards, particularly for PGMI students as prospective teachers.